Analysis of internal flow characteristics and entropy generation of low head bulb tubular pump - Tian, Xinyi; Cheng, Li; Jiao, Weixuan; Wang, Yuqi; Luo, Can (Frontiers in Energy Research, 2023)
To study the internal flow characteristics and energy characteristics of a large bulb perfusion pump. Based on the CFX software of the ANSYS platform, the steady calculation of the three-dimensional model of the pump device is carried out. The numerical simulation results obtained by SST k-ω and RNG k-ε turbulence models are compared with the experimental results. Finally, SST k-ω is selected for subsequent calculation. With the help of the flow line diagram and turbulent kinetic energy table of the whole flow channel of the pump device, the flow components of the pump device under different working conditions are analyzed, and the pressure and velocity distribution at the impeller and guide vane are analyzed by pressure cloud diagram and velocity cloud diagram. It is found that there are three high-pressure areas in the impeller and guide vane section, and the high-pressure regions are mainly distributed in the middle of the impeller channel. As the head decreases, the pressure at the impeller and guide vane positions decreases gradually, and the flow rate increases. Based on the entropy production principle, the wall entropy production and the distribution of mainstream entropy production at the impeller and guide vane parts are analyzed.